KARAKTERISTIK PERKEMBANGAN ANAK USIA DINI - rina nurasyiah; Cucu Atikah (Universitas Muhammadiyah Purwokerto, 2023)
Child is someone with unique characteristics. Early childhood is a very fundamental period for the development of a child, where at this time the development process runs rapidly. At this time children are ready to carry out various activities in order to understand and master their environment and is a golden age. This paper is a theoretical study of several references regarding the characteristics of early childhood. The purpose of this paper is to add insight and understanding of teachers and parents about how early childhood is absolutely. By understanding the characteristics of early childhood development, teachers and parents can place themselves in the development of the child, in other words, do not impose personal will on the child because it will greatly affect future development.